2011
DOI: 10.1523/jneurosci.2106-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Infant Brain Myelination with Magnetic Resonance Imaging

Abstract: Myelination, the elaboration of myelin surrounding neuronal axons, is essential for normal brain function. The development of the myelin sheath enables rapid synchronized communication across the neural systems responsible for higher order cognitive functioning. Despite this critical role, quantitative visualization of myelination in vivo is not possible with current neuroimaging techniques including diffusion tensor and structural magnetic resonance imaging (MRI). Although these techniques offer insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
351
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(388 citation statements)
references
References 43 publications
17
351
3
3
Order By: Relevance
“…At birth, the nervous system of the infant is immature since the myelination process is not finished (Eyre, 1992;Deoni et al, 2011), which means that the discriminative sense of touch probably lacks the specificity it has in adults. However, the unmyelinated system, which is evolutionarily older and encompasses temperature, pain and CT afferents (Uvn€ as-Moberg, 2012), may already be in place.…”
Section: Discussionmentioning
confidence: 99%
“…At birth, the nervous system of the infant is immature since the myelination process is not finished (Eyre, 1992;Deoni et al, 2011), which means that the discriminative sense of touch probably lacks the specificity it has in adults. However, the unmyelinated system, which is evolutionarily older and encompasses temperature, pain and CT afferents (Uvn€ as-Moberg, 2012), may already be in place.…”
Section: Discussionmentioning
confidence: 99%
“…The further maturation of NOT-DTN response properties seen as increase in peak activity, shortening of visual latencies and strengthening of the input of the ipsilateral eye leading to an improvement of the mhOKR during nasotemporal stimulation can probably be attributed to the maturation of cortical areas and their projections to the NOT-DTN. The long time course might correspond to the prolonged process of myelination and local circuit formation in primate cortex as revealed histologically and with magnetic resonance imaging (Rodman, 1994;CondĂ© et al, 1996;Gogtay et al, 2004;Kourtzi et al, 2006;Malkova et al, 2006;Deoni et al, 2011). Interestingly, area MT like primary sensory areas shows adult-like immunohistochemistry within the first postnatal month (Bourne and Rosa, 2006).…”
Section: Maturation Of the Optokinetic Reflex And Not-dtnmentioning
confidence: 93%
“…A late-developing brain center for socioemotional control (Giedd et al, 1996;Deoni et al, 2011), the amygdala is implicated in the pathophysiology of neurodevelopmental psychiatric disorders (Quirk and Gehlert, 2003;Amaral et al, 2008;Benes, 2010;Felix-Ortiz and Tye, 2014). Adult amygdala function and emotional behavior are altered by PS (Weinstock, 2008;Sadler et al, 2011), and several studies have identified effects of PS on the developing amygdala (Kraszpulski et al, 2006;Laloux et al, 2012).…”
Section: Introductionmentioning
confidence: 99%